This is what I used to know about it. - حەمەخان, شيروان علی (Sulaimani Journal for Humanities, 2019)
In this paper we try to discuss the relationship between ethnological science and the art of painting in the West Explain how this relationship has a direct impact on the process of self-renewal and criticism of the whole The process of painting dates back to the beginnings of modern classical art to modern art there has been. The beginnings of the ethnological influences on the art of painting were initially the introduction of foreign cultures The West was through the scientific expeditions of artists in the early nineteenth century with ethnologists Waltoani Assoya and Aqariaoa South America. The introduction of these different cultures is the new “Noao”. He introduced modern classical art, especially the Surrealists. But since the 1960s, the effect has been the same It was not the introduction of the name that became part of the art of painting, but the introduction of foreign cultures The West as a different culture with a different perspective should become part of the art of painting. That's what he did After the globalization process, other cultures should participate in the process of art production and not be marginalized.